Islam Hadhari – From The Non-Muslim Perspective (Jurnal Kemanusiaan, 2017)
ABSTRAKDatuk Seri Abdullah Ahmad Badawi presided as the Prime Minister on October 31, 2003; a smooth process of political exchange and transition for 16 months from former Prime Minister Tun Dr. Mahathir Mohamad, a statesman who had stood at the helm of the government for almost 22 years. After taking over the administration, Datuk Seri Abdullah introduced a few new agendas to show there are changes in continuity of national leadership including Islam Hadhari. In the context of multi-ethnic society, this policy is introduced to make the Muslim understand how progress is a part of Islam which includes modernity and values substance. At the same time, Islam Hadhari is also an approach which does not discriminate against the non-Muslim. There are ten principles put forward by the Prime Minister which the community must demonstrate so that development and modernization of the country are enjoyed and the fulfillment of livelihood and demands of their religions are carried on smoothly. This article examines Islam Hadhari from the non-Muslim perspective which includes the role and contributions of the community in order to ensure success of this agenda.